Application of Humic Acid and Gypsum Enhances Soil Nutrient Availability and Tomato (Solanum Lycopersicum) Yield in Mangrove-Derived Saline Soils - Bahiro, Badriyatul; Mindari, Wanti; Arifin, Moch. (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2025)
Background: This Research aims to evaluate the effect of humic acid and gypsum application on organic matter availability and the yield of tomato plants cultivated on mangrove forest soil. Methods: The research employed a Completely Randomized Design (CRD) in factorial pattern involving two primary factors. Results: Indicate that applying humic acid (1,124 g) and gypsum (18,75 g) can significantly influence the growth, productivity, and nitrogen uptake in tomato plants. Furthermore, the combination treatments of H3G3 (humic acid 0,124 g and gypsum 18,75 g) and H3G4 (humic acid 0,124 g and gypsum 25 g) yielded the highest number of tomato fruits, at 14.33 fruits. Additionally, the highest Vitamin C content (37,84 %) was detected in tomato fruits from the 0,124 g humic acid treatment. Conclusions: The combination of humic acid and gypsum significantly improves mangrove soil conditions by reducing salinity and increasing essential macronutriens like nitrogen and phosphorus. This synergy enhances nutrient retention and uptake, while gypsum supplies calcium and sulfur to correct acidic of saline soils. As a result, it creates a more fertile environment that supports healthy tomato growth and improves both yield quality and quantity.